Effects of m-nisoldipine on the activity and mRNA expression of four CYP isozymes in rats. (3rd July 2018) - Sun, Yupeng; Liu, Yanyan; Zhang, Xia; Wan, Changchen; Lyu, Tao; Zhang, Lantong
Abstract: 1. For the first time, a systemic in vivo investigation was employed to evaluate the potential effects of m -nisoldipine on activities of rat cytochrome P450 enzymes (CYP1A2, CYP2C11, CYP2D1 and CYP3A1) by both cocktail probe drugs and the quantitative real-time reverse-transcription polymerase chain reaction (RT-qPCR). 2. m -Nisoldipine-treated and blank control groups were respectively administered m -nisoldipine at the dosage of 2.5, 5 and 12.5 mg/kg and CMC-Na solution for 15 days consecutively, then they were given the probe drugs of caffeine, diclofenac, dextromethorphan and midazolam (all probes were 5 mg/kg) by p.o . The blood samples were collected at different times for liquid chromatography coupled with mass spectrometry (LC-MS) analysis. The corresponding pharmacokinetic parameters were applied to evaluate the effects of m -nisoldipine on the four CYP isoforms in vivo . In addition, RT-qPCR was performed to determine the effects of m -nisoldipine on the mRNA expression of CYPs in rat liver. Results indicated that high dose and middle dose of m -nisoldipine showed significant effects on all four CYPs and CYP2C11, respectively. Moreover, for CYP2D1 and CYP1A2, there were no significant effects found at either low or middle dose of m -nisoldipine. 3. This study could provide not only experimental evidence for potential clinical application of m -nisoldipine but also a practical strategy for assessing CYP-mediated drug–drug interactions.